Curcumin inhibition of the effects of Tip α induced cytokine expression in gastric cancer patients - Pattama Wongsirisin (2018)
© 2018 Elsevier B.V. Helicobacter pylori (H. pylori) is a major risk factor for gastric cancer. TNF-α inducing protein (Tip α) is an inflammatory factor of H. pylori. It can induce inflammatory cytokine secretion via the NF-kB signaling pathway. The aim of this study is to investigate whether curcumin, a natural NF-kB inhibitor, can reverse the effects of Tip α-induced cytokine expression in gastric cancer subjects both in vitro and ex vivo. The inhibitory effects of curcumin on cytokine expression were detected by Real time RT-PCR and ELISA. NF-kB activation was detected by immunocytochemistry and western blotting. Treatment of MKN-1 and KATOIII cell lines with Tip α showed significantly increased levels of TNF-α IL-6 and IL-8 in a dose-dependent manner. Tip α could significantly upregulate NF-kB nuclear translocation in both time-dependent and dose-dependent manners. Treatment of the cells with curcumin was able to block the effects of Tip α-induced cytokine expression along with NF-kB nuclear translocation. The ex vivo study using the primary culture obtained from tumor samples taken from patients also showed the same pattern with gastric cancer cell lines. This result suggests that curcumin can be used as chemopreventive agent for gastric cancer in H. pylori infected patients.